[tex]\displaystyle\bf\\1)\\\\\frac{8}{x+8} +\frac{64+x^{2} }{x^{2} -64} -\frac{8}{x-8} =\frac{8}{x+8} +\frac{64+x^{2} }{(x+8)(x-8)} -\frac{8}{x-8} =\\\\\\=\frac{8\cdot(x-8)+64+x^{2} -8\cdot(x+8)}{(x+8)(x-8)} =\frac{8x-64+64+x^{2} -8x-64}{(x+8)(x-8)} =\\\\\\=\frac{x^{2} -64}{x^{2} -64} =1\\\\\\2)\\\\\frac{x+8}{8} -1=\frac{x}{8} +\frac{8}{8} -1=\frac{x}{8} +1-1=\frac{x}{8} \\\\\\3)\\\\1:\frac{x}{8} =1\cdot \frac{8}{x} =\frac{8}{x} \\\\\\x=1,25[/tex]
[tex]\displaystyle\bf\\\frac{8}{x} =\frac{8}{1,25} =\frac{8\cdot 4}{5} =6,4\\\\\\Otvet \ : \ 6,4[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]\displaystyle\bf\\1)\\\\\frac{8}{x+8} +\frac{64+x^{2} }{x^{2} -64} -\frac{8}{x-8} =\frac{8}{x+8} +\frac{64+x^{2} }{(x+8)(x-8)} -\frac{8}{x-8} =\\\\\\=\frac{8\cdot(x-8)+64+x^{2} -8\cdot(x+8)}{(x+8)(x-8)} =\frac{8x-64+64+x^{2} -8x-64}{(x+8)(x-8)} =\\\\\\=\frac{x^{2} -64}{x^{2} -64} =1\\\\\\2)\\\\\frac{x+8}{8} -1=\frac{x}{8} +\frac{8}{8} -1=\frac{x}{8} +1-1=\frac{x}{8} \\\\\\3)\\\\1:\frac{x}{8} =1\cdot \frac{8}{x} =\frac{8}{x} \\\\\\x=1,25[/tex]
[tex]\displaystyle\bf\\\frac{8}{x} =\frac{8}{1,25} =\frac{8\cdot 4}{5} =6,4\\\\\\Otvet \ : \ 6,4[/tex]